Can vocational role models change the gendered perception of STEM VET occupations? Results from an intervention study in Germany - Beckmann, Janina [Verfasser]; Athanasiadi, Ermioni [Verfasser]; Granato, Mona [Verfasser] (My University, 2026)
"In the German vocational education and training (VET) system, female apprentices are strongly underrepresented in STEM professions, where there is also a general shortage of skilled workers. In this study, we look at whether a vocational role model intervention of apprentices visiting schools could reduce gender differences in students’ aspirations toward VET STEM professions and change their gendered perception of these occupations in terms of their occupational knowledge, self-efficacy, and perception of tasks as interesting. Based on a regional sample of male and female secondary school students in Germany surveyed in 2022 and 2023, our results indicate that students still hold gendered career aspirations, self-efficacy, and knowledge with Journal Pre-proof 1 respect to STEM VET occupations. Based on a non-equivalent control group design, we find that the role model intervention with mainly male role models can reduce these gendered perceptions to some extent, with female students developing greater occupational knowledge and higher career aspirations. These findings suggest that real-life vocational role models can serve as a promising career orientation approach in the context of VET to reduce gendered perceptions and aspirations in the career choice process." (author's abstract ; BIBB-Doku)
Keywords: P 1.1 Jugendliche; L 5 Beratung & Orientierung; G 2.4.5 Gender Mainstreaming; 370; Jugendlicher; Berufsorientierung; Berufswahlverhalten; Berufswahlmotiv; Berufswunsch; Geschlechtsspezifische Faktoren; MINT-Berufe; Vorbild